Untersuchungen über Gallmücken. XII. Rhabdophaga clavifex (Kieffer, 1892), Rhabdophaga repenticola Stelter n. sp. und ihre Gallen (Diptera: Itonididae, Cecidomyiidae). - Stelter, Helmut; Buhr, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1964)
There are given additional notes on taxonomy and galls of a gall midge already known from hairy broad-leaved willows and described as new a related species living in similar galls on Salix repens. The seasonal change in shape of the galls and differences between the two species are mentioned. Nomenclatural Acts repenticola Stelter, 1964 (Rhabdophaga), spec. n.